Creative And Innovative Abilities of Tenth Grade Senior High School Student In Solving SPLTV Tasks - Yudha, Firma; Azizah, Siti Nur (Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, 2023)
This research discusses the level of students' creative and innovative abilities according to the indicators in 21st century learning which aims to determine the effect of realistic mathematics learning and describe the level of students' innovative creative thinking skills. The method used in this research is mixed method. The results showed that based on the results of hypothesis testing there was a significant effect with the results of Assym Sig 0.000 <0.05, meaning that realistic mathematics learning was able to improve students' creative and innovative thinking skills and based on data analysis there were 3 students who had level 0 creative and innovative thinking skills, 17 students who had level 1 creative and innovative thinking skills, 7 students who had level 2 creative and innovative thinking skills, and 1 student who had level 3 creative and innovative thinking skills.